Report writing in business - Bentley, Trevor J., ....- (London : Kogan Page, 1990)
Written reports are the most frequently used method of presenting information to management and are, therefor, crucial to effective business communication. The ability to write clear, comprehensive reports is al skill required by all managers. Knowing what you want to way, to whom and the reason, is futile if you cannot say it effectively. This concise and informative book teaches you to mster the techniques necessary for purposeful report writing. It examines a variety of methods and approaches, and provides solid advice on content, layout and presentation. The author stresses the importance of knowing: what your aims are, who your audience is and how it should be approached, what you want to communicate, how to write an effective report. Useful tips on clarity, simplicity of language, brevity and precision of expression, combined with extensive use of examples of different types of report give managers an insight into the methods of effective report writing.